Application of hybrid-Trefftz finite element method to frictional contact problems - Qin, Qing-Hua; Wang, Ke-Yong (Computer Assisted Methods in Engineering and Science, 2022)
A contact algorithm, based on the hybrid-Trefftz (HT) finite element method (FEM), is developed for the solution of contact problems with Coulomb friction. Contact conditions are directly imposed with the aid of a direct constraint approach. On the other hand, static condensation technique is used to reduce the contact system to a smaller one which involves nodes within the potential contact surfaces only so that it may save computing time significantly. The final contact interface equation is constructed by considering contact conditions as additional equations. An incremental-iterative algorithm is introduced to determine proper load increments and find correct contact conditions. The applicability and accuracy of the proposed approach are demonstrated through three numerical problems.